1993 Annual Report - Rowan Tree Church (Northridge, CA: Rowan Tree Church, 1993)
The cover of eleventh annual report provides a table of contents, which includes: The General Manager’s report; The Eldermentor’s report; The Board President’s report; The Board Vice- President’s report; The Board Secretary’s report; The Board Treasurer’s report; The Board Scribe’s report; Report from The Unicorn editor; Report from RT News editor; Librarian’s report; The Galadhrim Society reports; Report from the editors of The Littlest Unicorn.
Rowan Tree Church Annual Report, 1993
This digital asset was created from the original digital scans by Rev. Paul V. Beyerl and provided to the Valdosta State University, Archives & Special Collections to be part of their Rowan Tree Church Periodicals Collection of the New Age Movements, Occultism, and Spiritualism Research Library. The Rowan Tree Church is an earth-based religion founded by Rev. Paul Beyerl, a Third Degree Initiate in the Alexandrian Tradition of Wicca, and incorporated on February 4, 1980 in Minneapolis, Minnesota. The church is now based in Kirkland, Washington with many communities throughout the United States and Canada. The roots of the Church extend back to 1976 which Rev. Beyerl began teaching Wicca, Astrology, and Herbalism out of his home. The Church's religion, The Tradition of Lothloriën, embraces inclusiveness and accepts all people regardless of faith, sexual orientation, race, or gender, a noted departure from early Alexandrian Wicca. The Tradition has elements of Herbalism, Astrology and Tibetan Buddhism in its structure, and is deeply rooted in its Mystery School, an in-depth study program that leads to Ordination, and the Hermit's Grove, its educational and publishing entity. Noted publications are The Unicorn, The Littlest Unicorn for children, and The Hermit’s Lantern.
Keywords: Rowan Tree Church--History; Rowan Tree Church--Appropriations and expenditures; Lothloriën (Wiccan sect); Mystery School of Lothloriën; Wicca--Study and teaching; Littlest Unicorn (Rowan Tree Church); Galadhrim Society.; Prison Outreach Program.; Annual reports.